General approaches in health disaster and emergency planning and existing health plans in Turkey - Sıdıka Tekeli Yeşil (Turkish Society of Public Health Specialists, 2017)
This report aims to inform health workers about the general principles of health disaster and emergency planning, and to familiarize them with the existing plans in Turkey. The health sector has an important role in disaster management. All natural and technological hazards and complex emergencies have a direct or indirect impact on human health and wellbeing. Health systems have a vital role in responding to these disasters. Health disaster plans are important tools for disaster management. In the introduction of this report, the steps of a disaster management cycle and the general principles of emergency planning in health systems will be reviewed. Subsequently, health disaster plans, at national, provincial and hospital levels will be discussed. Finally, these plans will be assessed and some recommendations will be provided. Key words: Disaster, disaster management, health disaster, emergency plans